We dream of space - Kelly, Erin Entrada (Greenwillow Books, 2020)
In 1986, Cash, Fitch, and Bird Thomas are in seventh grade. Cash loves basketball, but just broke his wrist and is in danger of failing seventh grade for the second time. Fitch spends every afternoon at the local arcade and deals with an explosive temper. His twin sister, Birdie, dreams of being NASA's first female shuttle commander, but feels like she's disappearing. They all exist in their own little orbits in their tense home, with little in common. But after the disastrous launch of the Space Shuttle Challenger, their lives change in unexpected ways.